Emerging Risks and Strategic Challenges in the Insurance Sector - Cernit, Rodica; Moroi, Tatiana; Margineanu, Aureliu (The Journal of Accounting and Management, 2024)
Insurance sector, essential for economic stability and financial protection, faces numerous significant risks and challenges generated by rapid and complex changes. The aim of the paper is to deepen the understanding of emerging risks affecting the insurance sector and to provide strategic solutions for insurance companies. These challenges have a significant impact on the way insurance companies structure their product portfolios and define their business models. The existing concepts in the specialized literature are emerging risks and strategic challenges regarding digital transformation. The paper combines qualitative and quantitative methods to understand their complexity. The research results can be obtained by developing strategies for diversifying insurance portfolios to cope with economic uncertainties. The implications, expressed in the form of conclusions and recommendations, can guide academic and administrative development. The value of the work is defined by its impact on the understanding and management of emerging risks in the insurance sector.